Grupo mediano de personas. (UNED, 2024)
Aparece de izquierda a derecha de pie. Max Araya Garita, Vinicio Quesada Segura, Cristian Álvares Pérez, Osvaldo Solano Peralta, Mario Mora Saborío, Cinthia Mora Fuentes, Lizette Benavides Bonilla, Alexandra Sabria Araya